2022
DOI: 10.25259/sni_208_2022
|View full text |Cite
|
Sign up to set email alerts
|

Frontal aslant tract: Anatomy and tractography description in the Mexican population

Abstract: Background: The aim of the study was to describe the origin, course, and termination of frontal aslant tract (FAT) in the Mexican population of neurosurgical referral centers. Methods: From January 2018 to May 2019, we analyzed 50 magnetic resonance imaging (MRI) studies in diffusion tensor imaging sequences of patients of the National Institute of Neurology and Neurosurgery “Manuel Velasco Suárez.” Five brains were fixed by the Klingler method and dissected in the neurosurgery laboratory of the Hospital C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Although previous studies have shed light on the structure and function of the FAT, a populationbased investigation of individual differences in FAT remains to be conducted. While several studies have suggested that the pars opercularis is the primary source of connectivity in the FAT 3,6 , other studies have shown that in some cases, the pars triangularis may be the primary contributor of fibers 7 . These discrepancies suggest that there could be substantial individual variation in the distribution of FAT fibers.…”
Section: Introductionmentioning
confidence: 97%
“…Although previous studies have shed light on the structure and function of the FAT, a populationbased investigation of individual differences in FAT remains to be conducted. While several studies have suggested that the pars opercularis is the primary source of connectivity in the FAT 3,6 , other studies have shown that in some cases, the pars triangularis may be the primary contributor of fibers 7 . These discrepancies suggest that there could be substantial individual variation in the distribution of FAT fibers.…”
Section: Introductionmentioning
confidence: 97%
“…Although previous studies have shed light on the structure and function of the FAT, a population‐based investigation of individual differences in FAT remains to be conducted. While several studies have suggested that the pars opercularis is the primary source of connectivity in the FAT (Catani et al, 2012 ; Szmuda et al, 2017 ), other studies have shown that in some cases, the pars triangularis may be the primary contributor of fibers (Marian‐Magaña et al, 2022 ). These discrepancies suggest that there could be substantial individual variation in the distribution of FAT fibers.…”
Section: Introductionmentioning
confidence: 99%